2004
DOI: 10.1037/0022-3514.86.2.334
|View full text |Cite
|
Sign up to set email alerts
|

Do People Agree About the Causes of Behavior? A Social Relations Analysis of Behavior Ratings and Causal Attributions.

Abstract: Two studies examined consistency and agreement in behavior ratings and causal attributions. In Study 1, participants (N = 280) engaged in a series of getting-acquainted conversations in one of 3 communication media (face-to-face, telephone, computer mediated); in Study 2, participants (N = 120) engaged in a competitive group task. In both studies, participants rated themselves and their interaction partners on a set of behaviors and then made attributions about the causes of those behaviors. The major findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…In the bandage condition, the bandage makes the injury more salient [10]. The findings are also consistent with the view that people tend to explain others' behaviour in the same way they explain their own behaviour [12]. Most participants would not have experienced a brain injury, whereas all would have experienced adolescence, which is the preferred explanation in the no bandage condition.…”
Section: The Effect Of Visibilitysupporting
confidence: 84%
See 1 more Smart Citation
“…In the bandage condition, the bandage makes the injury more salient [10]. The findings are also consistent with the view that people tend to explain others' behaviour in the same way they explain their own behaviour [12]. Most participants would not have experienced a brain injury, whereas all would have experienced adolescence, which is the preferred explanation in the no bandage condition.…”
Section: The Effect Of Visibilitysupporting
confidence: 84%
“…Robins et al [12] showed that people's attributions for others' behaviour reflects their attributions for their own behaviour. Applied to brain injury, this finding implies that when a person with brain injury looks like a normal adolescent and they lose their temper, observers may attribute the behaviour to the person's adolescence, because they performed similar behaviours when they were adolescents.…”
Section: Cognitive Processes Affecting Behaviour Attributionsmentioning
confidence: 98%
“…Crittenden, 1983;Johnson, & Drobny, 1985;Griffin, Babin, & Attaway, 1996;Pierro, Mannetti, Kruglanski, & Sleeth-Keppler, 2004;Robins, Mendelsohn, Connell, & Kwan, 2004;Wang, 2004). Of the studies in motivation, framing, learning, attribution, attitude, and combinations therein, this review contains those that contribute strongly to the understanding of attribution bias, which is quite relevant to the topic at hand.…”
Section: Attribution Theorymentioning
confidence: 98%
“…''Individuals get too much credit when things go well and too much blame when things go poorly'' (Moon and Conlon 2002, p. 33). Finally, Robbins et al (2004) concluded from experiments with unfamiliar individuals in relatively brief interactions where the emotional stakes were low, that people are consistent in the way they perceive and explain (attribute) behaviour, regardless of the particular interaction situation or the particular individual whose behaviour is judged. This suggests that it is ''general schemas, such as implicit theories, [that] drive causal attributions'' (Robbins et al 2004, p. 341), rather than complex, person-and situation-specific models, such as proposed, for example, by Mayer et al (1995).…”
Section: Building Trustmentioning
confidence: 99%